A CORRELATION OF LEARNING STYLES AND VOCABULARY ACHIEVEMENT - Oksattridywi, Mutriza (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research focused on correlation of learning styles and vocabulary achievement. The aim of this research was to know whether significant or not the correlation of visual, auditory, and kinesthetic learning style to vocabulary achievement. The research was conducted to Year-11 students of Madrasah Aliyah Khulafaur Rasyidin in academic year 2016/2017. The data were collected through a questionnaire about learning style and a test of vocabulary. Significance of the correlated variable is computed using t-test. If t-value is higher than t-table, the correlation is significant. The t-value was compared to t-table. The findings are t-value of visual learning style was 8.02, for auditory learning style 2.46, while t-value of kinesthetic learning style was 0.51. The value of t-table was 2.101 at significant level 5% and df 18. Based on the results, it was found there is significant correlation of visual learning style to vocabulary achievement. There is significant correlation also for auditory learning style and vocabulary achievement. There is no significant correlation of kinesthetic learning style and vocabulary achievement.Keywords: Auditory, Visual, Kinesthetic, Vocabulary Achievement